Physical Stability Test of Liquid Soap Preparation from Avocado Seed Oil (Persea americana Mill.) - Kariem, Nazli; Djuwarno, Endah Nurrohwinta; Latif, Multiani S (Jurnal Farmasi Teknologi Sediaan dan Kosmetika, 2025)
Avocado seed oil has numerous benefits and contains secondary metabolites such as alkaloids, flavonoids, tannis, saponins, terpenoids or steroids, and phenolics, which act as natural antioxidants, as well as vitamin E, wich can be used as a skin moisturizer. The flavonoid content as an antioxidant and vitamin E moisturizing the skin can be used to produce liquid soap formulations. This study aims to determine the Physical Stability Test of Liquid Soap Made from Avocado (Persea americana Mill.) Seed Oil. This research was an experimental laboratory study using Avocado Seed Oil and HPMC as a gel base with consentration of 2%. The outcome of liquid soap formulation was tested for physical stability, including organoleptic properties, homogeneity, pH, viscosity, spreadability, irritation, foam height, hedonic properties, and cycling tests. The results showed that the liquid soap formulation was clear, had characteristic avocado smell, a semi-solid texture, homogeneity, and stability at room temperature storage for 21 days, and stability at 4֯C and 40֯C storage for six cycles.